FACTORS RELATED TO COMPLIANCE WITH THE IMPLEMENTATION OF COVID-19 VACCINATION AT THE AGE OF 18 TO 78 YEARS IN SETIA ASIH V ILLAGE, TARUMAJAYA DISTRICT, BEKASI REGENCY - Jihan Musliha; Siti Rafingah (Afiat, 2022)
The increase in the corona virus in Indonesia has made the Government issue policy efforts to accelerate tackling Covid-19, the policy is vaccination. The government requires the public to be vaccinated in both doses, one, two, and booster, the factors that influence people's compliance to follow the vaccine one of which is knowledge in this case compliance plays an important role to reduce mortality and excessive nursing. The purpose of the study was to find out the factors related to compliance with Covid-19 vaccination in rt.01/rw.011 at the age of 18 to 78 years in the village of Setia Asih, Tarumajaya sub-district, Bekasi district. Correlative descriptive research method with a cross sectional approach the population in this study was 225 respondents, the sample was taken by purposive sampling technique as many as 144 respondents. The analysis used univariate and bivariate using chi-square with a = 5%. The results showed that the occupation was p0.001 <0.05, and knowledge was p0.015 <0.05. The conclusions of this study have a relationship between work and knowledge with Covid-19 vaccination compliance, while gender, age and education factors have no relationship with Covid-19 vaccination compliance in Rt. People who have not carried out the second dose or booster vaccination, are expected to continue to follow the Covid-19 vaccination to maintain immunity against the transmission of a disease.